Parents' Perception of Bedtime Stories as An Effort to Build Early Literacy - Indar, Indrawati; Purnama, Sigit; Hardiyanti, Widya Dwi (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2024)
Early literacy is a child's ability to interact with information across media, forming a foundation for cognitive, language, and social development. Research highlights that bedtime storytelling plays an important role in stimulating children's literacy development. However, do parents have the same perspective? This study aims to explore parents' perception of bedtime storytelling as a tool to foster early literacy in children. A mix method was used, with data collected through surveys containing indicators to measure parental perceptions. These findings reveal three important points: First, parents generally have the same and conceptually accurate that bedtime storytelling is important. Second, there is variation in parents' understanding of early literacy, with few fully understanding the concept. Third, parents have a positive perception of the role of bedtime storytelling in building early literacy, although they face challenges such as limited leisure time and a lack of effective storytelling techniques. The study emphasizes the importance of proactive efforts by parents and other stakeholders to overcome these barriers and include bedtime storytelling as a routine habit. This practice can serve as a powerful and fun way to improve children's early literacy skills, fostering a lifelong love of learning and reading.